Anti-inflammatory effect of methanol extracts of hemp leaf in IL-1β-induced synovitis - Duangnin N. (2017)
© Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria. All rights reserved. Purpose: To examine the effectiveness of some hemp (Canabis sativa) leaf extracts as an antiinflammatory agent on synovitis in vitro. Methods: Synovial fibroblast cell line SW982 was induced with 5 ng/mL of interleukin 1-beta (IL-1β) to trigger cellular inflammation. The cells were then treated with prepared extracts of hemp (Canabis sativa) leaf originating from three different cultivation sites with varying proportions of terpenoids and cannabinoids, especially cannabidiol (CBD) and tetrahydrocannabinol (THC). Nitric oxide (NO) and prostaglandin E2 (PGE2) production as well as expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and IL-1β genes were determined. Results: All hemp extracts reduced the production of NO and PGE2 in a dose-dependent manner. The expressions of iNOS, COX-2 and IL-1β genes were significantly decreased by the hemp extracts. This effect was likely related to the amount of sesquiterpenoids and THC. The extract from Huai Hoi (HH) cultivar showed the most promising results for further studies. Conclusion: The extracts of hemp leaf substantially reduces the level of biomarkers for inflammation in vitro. Therefore, the extracts have a potential application as an inflammatory counteractant in synovitis.